An overview of circular economy management approach for sustainable construction and demolish waste management - Alazaiza, Motasem Y. D.; Albahnasavi, Ahmed; Eyvaz, Murat; Al Maskari, Tahra; Amr, Salem S. Abu; Nassani, Dia Eddin; Jazar, Mohammed Shadi Abu (Global Network Environmental Science & Technology, 2024)
Waste generation from the construction industry has been recognized as a key factor in environmental deterioration. Excessive waste in the construction field is a direct outcome of unsustainable production and consumption practices, typically ending up in landfills. To tackle this problem, a circular economy management approach has been proposed as a solution for sustainable construction and demolition waste management. This review outlines the strategy of the circular economy to promote sustainable management of construction and demolition waste. The circular economy management strategy emphasizes the importance of reducing waste production and promoting the reuse and recycling of materials. This approach also promotes the use of sustainable materials and the implementation of effective waste management practices during construction and demolition. The circular economy management approach to sustainable handling of construction and demolition waste involves several key strategies. These include embracing sustainable design and construction methods, encouraging material reuse and recycling, and establishing efficient waste management systems. These strategies require the cooperation and involvement of all stakeholders in the construction and demolition process, including architects, contractors, developers, and waste management companies. The circular economy management approach provides a promising framework for achieving the objectives of effective waste management and sustainable construction. By promoting sustainable patterns of production and consumption, this approach can reduce the environmental impact of the construction industry while generating economic benefits for stakeholders. However, successful implementation of this approach requires strong regulatory support and the willingness of all stakeholders to adopt sustainable practices.
Keywords: Sustainability; Circular economy; Construction and demolish waste. 3R. recyclable materials